Use of conjoint analysis to determine the impact of logotype colour, and the type, duration and price of a street performance on consumer purchase decisions - Piko, Maja; Toros, Jani; Stankovič Elesini, Urška (Journal of Graphic Engineering and Design, 2017)
The aim of our research was to determine how colour impacts the effectiveness of a logotype for a particular activity and which colour used is strong, stable, associative and “playful”, and thus the most appropriate for presenting a selected activity. For the purpose of this research, a logotype for a circus artist was designed using four colour variations, while conjoint analysis was used to identify the colour preference of a specific logotype. Besides colour, three additional attributes were chosen: the type, duration and price of a performance. Three or four levels were specified for every attribute. The results of the survey showed that colour is the not the most important of the four attributes, but that it does have a certain effect on a customer’s decision. In the analysis, most respondents choose the red logotype, an outdoor performance, and the longest duration and the lowest price of a performance. The most important of the four attributes for respondents was the price of a performance, followed by the duration of a performance, the content/type of a performance and finally the colour of the associated logotype. The preference of respondents was improved by testing combinations of the four attributes and levels, where the colour blue was replaced with red. The research opens possibilities for further research regarding the impact of colours on subconscious decisions.